Can Serum Anti-Mullerian Hormone Level and LH / FSH Ratio Be Predictive of Clinical Pregnancy Through Intracytoplasmic Sperm Injection - Embryo Transfer? - Elgun, Tugba; Karacan, Meric; Sandal, Asiye Izem; Irez, Tulay (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: To compare clinical pregnancy rate through ICSI-ET between polycystic ovarian syndrome patients and women with normal ovaries (control group). We also investigated whether serum Anti-Müllerian hormone level or LH/FSH ratio may predict clinical pregnancy rate in both groups. Study Design: In this retrospective study, endocrine/ clinical parameters and cycle characteristics of women with polycystic ovarian syndrome (n=32) and women with normal ovaries (n=115) aged <40 years were evaluated. Results: Clinical pregnancy rate in polycystic ovarian syndrome group did not differ from that in the control group (31.3% vs. 32.2%, p>0.05, respectively). The LH/FSH ratio was significantly higher in women who conceived compared to women who did not in the polycystic ovarian syndrome group (0.9 vs. 0.6, respectively, p=0.4). The cut-off value of 0.6 in the LH/FSH ratio predicted clinical pregnancy with a specificity of 76% and a sensitivity of 65% in the polycystic ovarian syndrome group. Anti-Müllerian hormone was significantly higher in women who conceived compared to women who did not in the control group (4.0 ng/mL vs. 2.1 ng/mL, respectively, p=0.4). Conclusion: Polycystic ovarian syndrome patients have a similar clinical pregnancy rate with women having normal ovaries through ICSI-ET. The LH/FSH ratio assessed prior to ovulation induction was significantly higher in pregnant polycystic ovarian syndrome patients compared to polycystic ovarian syndrome patients who did not conceive. Anti-Müllerian hormone level was significantly higher in pregnant women compared to non-pregnant women with normal ovaries.